Biomechanical mechanism of reduced aspiration by the Passy-Muir valve in tracheostomized patients following acquired brain injury: Evidences from subglottic pressure - Han, Xiaoxiao; Ye, Qiuping; Meng, Zhanao; Pan, Dongmei; Wei, Xiaomei; Wen, Hongmei; Dou, Zulin (Frontiers in Neuroscience, 2022)
Objective: Aspiration is a common complication after tracheostomy in patients with acquired brain injury (ABI), resulting from impaired swallowing function, and which may lead to aspiration pneumonia. The Passy-Muir Tracheostomy & Ventilator Swallowing and Speaking Valve (PMV) has been used to enable voice and reduce aspiration; however, its mechanism is unclear. This study aimed to investigate the mechanisms underlying the beneficial effects of PMV intervention on the prevention of aspiration. Methods: A randomised, single-blinded, controlled study was designed in which 20 tracheostomized patients with aspiration following ABI were recruited and randomised into the PMV intervention and non-PMV intervention groups. Before and after the intervention, swallowing biomechanical characteristics were examined using video fluoroscopic swallowing study (VFSS) and high-resolution manometry (HRM). A three-dimensional (3D) upper airway anatomical reconstruction was made based on computed tomography scan data, followed by computational fluid dynamics (CFD) simulation analysis to detect subglottic pressure. Results: The results showed that compared with the non-PMV intervention group, the velopharynx maximal pressure (VP-Max) and upper esophageal sphincter relaxation duration (UES-RD) increased significantly (P<0.05), while the Penetration-Aspiration Scale (PAS) score decreased in the PMV intervention group (P<0.05). Additionally, the subglottic pressure was successfully detected by CFD simulation analysis, and increased significantly after two weeks in the PMV intervention group compared to the non-PMV intervention group (P<0.001), indicating that the subglottic pressure could be remodeled through PMV intervention. Conclusions: Our findings demonstrated that PMV could improve VP-Max, UES-RD and reduce aspiration in tracheostomized patients, and the putative mechanism may involve the subglottic pressure.